Literature Review: The Importance of Patients Satisfaction in Hospital Quality Management - Suci Dwi Yanti; Alifa Ainaya Gafar; Mujtahidah Salim (International Journal of Science Technology and Health, 2024)
Introduction: Hospital is a health service institution that provides comprehensive health services for individuals, including inpatient, outpatient and emergency services. Patient satisfaction is measured through emotional responses, such as feelings of joy and satisfaction, that arise in patients because their needs, hopes and desires are met in receiving health services. There is a link between hospitals, patient satisfaction, and quality management; where hospital quality management has a significant role in influencing patient satisfaction and service quality. This research uses a literature review method with sources from Google Scholar using the keyword "The Importance of Patient Satisfaction in Hospital Quality Management". The research results showed that three aspects, namely staff communication, hospital responsiveness, and environmental cleanliness and comfort, were proven to have an impact on hospital quality management.